Animal Emotions How They Drive Human Behavior - Montag, Christian (punctum books, 2020)
Animal Emotions: How They Drive Human Behavior gives a concise overview of ancient mammalian emotions deeply rooted in the human brain. Jaak Panksepp, a world-renowned neuroscientist, dedicated his life career to the study of mammalian emotions and he carved out seven distinct emotional systems he called seeking, lust, care, and play (positive emotions), and fear, anger, and sadness (negative emotions), all exerting a tremendous influence on human behavior.Christian Montag, a neuroscientist and psychologist, and a long-time collaborator of Jaak Panksepp, revisits together with Kenneth L. Davis, one of Jaak's PhD students, Panksepp's theories and provides the reader with new insights into the nature of emotions and their role as survival tools, both for animals and for humans. They also raise new questions about the background of the research field Jaak Panksepp coined "Affective Neuroscience." How are personality and psychopathology linked to animal emotions? Do animals feel the same way as we do? What are our emotional needs in a digital society, and what is key to a happy life?